2018
DOI: 10.7547/16-075
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lower-Extremity Arterial Calcification in Patients with Diabetes Mellitus Complicated by Foot Disease at an Urban US Tertiary-Care Center

Abstract: The results of this investigation increase the body of knowledge with respect to the evaluation and treatment of diabetic foot disease and may lead to future investigations on the topic of lower-extremity arterial calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…On the other hand, the higher ABIs could be indicative of MAC, which is considered by some researchers to be of similar concern as PAD with regard to cardiovascular events (Nishimura et al, 2016;Suominen et al, 2008). Although MAC is sometimes regarded to be likely only if ABIs are > 1.40 (Bundó et al, 2013;Chen et al, 2016), cutpoints of 1.30, 1.40, and 1.50 have been investigated as prospective cutpoints (Suominen et al, 2008), and even lower ABI cutpoints of 1.20 (McAra et al, 2017) and 1.10 (Cardenas et al, 2018) have been regarded as indicating MAC. Under these circumstances, it is difficult to interpret midrange ABI values with confidence.…”
Section: Issues Associated With Cutpointsmentioning
confidence: 99%
“…On the other hand, the higher ABIs could be indicative of MAC, which is considered by some researchers to be of similar concern as PAD with regard to cardiovascular events (Nishimura et al, 2016;Suominen et al, 2008). Although MAC is sometimes regarded to be likely only if ABIs are > 1.40 (Bundó et al, 2013;Chen et al, 2016), cutpoints of 1.30, 1.40, and 1.50 have been investigated as prospective cutpoints (Suominen et al, 2008), and even lower ABI cutpoints of 1.20 (McAra et al, 2017) and 1.10 (Cardenas et al, 2018) have been regarded as indicating MAC. Under these circumstances, it is difficult to interpret midrange ABI values with confidence.…”
Section: Issues Associated With Cutpointsmentioning
confidence: 99%
“…Our protocol successfully captured initial symptom assessment (HIS-r) within 72 h of ED evaluation, at which point participants reported a high total symptom severity. 32 Current research demonstrates 33 , 34 that a higher symptom severity immediately after concussion predicts a prolonged recovery. In our sample of women who experienced IPV-related strangulation, none of our participants reported a low symptom severity or reported as symptom free during any point in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that radiography and computed tomography can be used to detect ectopic calcification in arteries of diabetic subjects 17,18 . In the present study, we used histology and a nanomaterial-based approach to examine the formation of mineralo-organic particles in human arteries of diabetic subjects.…”
Section: Ectopic Calcification and Formation Of Mineralo-organic Part...mentioning
confidence: 99%